Linking species‐level network metrics to flower traits and plant fitness. (14th January 2020) - Lázaro, Amparo; Gómez‐Martínez, Carmelo; Alomar, David; González‐Estévez, Miguel A.; Traveset, Anna
Abstract: Theoretical models indicate that the structure of plant–pollinator networks has important implications for the reproduction and survival of species. However, despite the growing information on the mechanisms underlying such a structure, it is still difficult to predict the functional consequences of species' structural positions in these networks. From the plant perspective, species position and roles in pollination networks might be related to traits describing flower attractiveness, availability and dependence on pollinators. In turn, both network metrics and plant traits might influence plant species fitness. During two field seasons, we collected data from the 23 most abundant plant species in a rich coastal community, to evaluate the association between population and floral traits (floral abundance at population level and flowers per individual, flower shape and size, flowering length, nectar volume, pollinator dependence), species‐level network metrics (linkage level, specialization – d ′–, weighted closeness centrality, network roles related to modularity) and plant fitness (seeds/flower, seed weight). Flowering length, flower size, flower abundance and pollinator dependence were positively related to greater generalization, as measured by various indices. More abundant species and those with larger flowers showed higher linkage levels (i.e. higher number of pollinator species), whereas longer flowering periods were negatively related to d ′ and positively related to closeness centrality and important roles in the network. Likewise, plants species more dependent on pollinators occupied more central positions in the network. Furthermore, centrality in the networks was significantly associated with plant fitness. Specifically, central species in the network produced more and heavier seeds than the others. However, other plant traits, such as flower size and pollinator dependence had additional direct effects on seed production. Synthesis . Our study highlights how population and floral traits define the positions and roles of species structuring the pollination communities. Moreover, the relationships between network metrics and plant reproduction indicate, for the first time, the functional implications of these structural positions at the interspecific level of community assembly. Abstract : Our study highlights how population and floral traits define the positions and roles of species structuring the pollination communities. Moreover, the relationships between network metrics and plant reproduction indicate, for the first time, the functional implications of these structural positions at the interspecific level of community assembly. Translated Abstract: Resumen Los modelos teóricos indican que la estructura de las redes planta‐polinizador tiene implicaciones importantes para la reproducción y supervivencia de las especies. Sin embargo, pese a que cada vez existe más información sobre los mecanismos subyacentes a dicha estructura, todavía estamos lejos de poder predecir las consecuencias funcionales de las posiciones estructurales de las especies en las redes. La posición y los roles de las especies de plantas en las redes de polinización pueden estar relacionados con rasgos que describen el atractivo y la disponibilidad de sus flores, así como con la dependencia de los polinizadores para su reproducción. A su vez, tanto las métricas de la red como los rasgos de las especies pueden influir en su éxito reproductivo. Durante dos temporadas de campo, recolectamos datos de las 23 especies de plantas más abundantes de una comunidad costera rica en especies, para evaluar la asociación entre los rasgos florales y poblacionales de las especies de plantas (abundancia floral a nivel de población y flores/individuo, forma y tamaño de la flor, duración de la floración, volumen de néctar, dependencia de polinizadores), las métricas de red a nivel de especie (nivel de enlace, especialización –d´–, centralidad, roles de red relacionados con la modularidad) y su éxito reproductivo (semillas/flor, peso de semilla). La duración de la floración, el tamaño de la flor, la abundancia de flores y la dependencia de los polinizadores se relacionaron positivamente con una mayor generalización, medida con diferentes índices. Las especies más abundantes y aquellas con flores más grandes mostraron niveles de enlace más altos (es decir, un mayor número de especies de polinizadores), mientras que los períodos de floración más largos se relacionaron negativamente con d' y positivamente con la centralidad y los roles importantes en la red. Asimismo, las plantas más dependientes de polinizadores ocuparon posiciones más centrales en la red. Además, la centralidad de las especies en las redes se asoció significativamente con el éxito reproductivo de las plantas. Específicamente, las especies centrales en la red produjeron más semillas y más pesadas que las otras especies. Sin embargo, otros rasgos de las plantas, como el tamaño de las flores y la dependencia de los polinizadores tuvieron efectos directos adicionales sobre la producción de semillas. Síntesis . Nuestro estudio destaca cómo la población y los rasgos florales definen las posiciones y roles de las especies que estructuran las comunidades de polinización. Además, las relaciones entre las métricas de la red y el éxito reproductivo de las plantas indican, por primera vez, las implicaciones funcionales de estas posiciones estructurales al nivel inter‐específico de ensamblaje de comunidades.